External quality assessment of genetic testing for hereditary hearing loss in Shanghai and other regions - Yun Bao; Pengyin Zhang; Jing Quan; Xue Yang; Yanqun Xiao; Xiaobo Hu (Practical Laboratory Medicine, 2025)
Objectives: Hereditary hearing loss is one of the most common birth defects in humans. Genetic screen in pregnant women and newborns could provide prenatal intervention or guidance on the early diagnosis and treatment. Currently, this screen has been widely applied; however, its accuracy and reliability have not been determined. The objective of this pioneering study was to evaluate the performance of clinical laboratories in Shanghai and other regions for their ability to analyze the genetic variants related with hearing loss. Methods: The EQA program were carried out twice a year. We generated a sample panel consisting of five dry blood spots with genomic DNA from different cell lines with normal whole blood as the matrix. The panel included four samples with nine different pathogenic variants of GJB2, GJB3, SLC26A4 as well as mitochondria DNA (mt DNA) and one wild type sample. The panel was distributed to participant laboratories for genetic analysis, and the results were compared and scored. Results: Thirty and twenty-nine clinical laboratories participated in the two EQA scheme in 2023, respectively. 28 (93.33 %) and 27 (93.10 %) laboratories achieved an acceptable or superior performance score(≥80). There were ten errors with eight false-negative and two false-positive results in the first EQA scheme, and seven errors with five false-negative and two false-positive in the second EQA scheme. Conclusions: The results indicate that the majority of the clinical genetic analysis of deafness-related genes were satisfactory in China, while some participant laboratories needed further improvement. In addition, external quality assessment was demonstrated as an important method for monitoring the performance of clinical laboratories.